FRI0263 PTX3 and TSG-6 Identify Specific Disease Subsets in Anca-Associated Vasculitides. (9th June 2015) - Ramirez, G.A.; Blasi, M.; Bottazzi, B.; Valentino, S.; Tombetti, E.; Sabbadini, M.G.; Rovere-Querini, P.; Mantovani, A.; Manfredi, A.A.
Abstract : Background: More accurate Anti Neutrophil Cytoplasmic Antibodies (ANCA) – associated vasculitides (AAV) biomarkers could yield clues about the pathogenesis and improve patients monitoring during follow-up. The long pentraxin PTX3 is an emerging marker of acute inflammation and vessel injury. Tumor Necrosis Factor-Stimulated Gene-6 (TSG-6) is an anti-inflammatory signal often co-expressed with PTX3 by leukocytes and endothelial cells. Objectives: To evaluate the possible correlations among PTX3, TSG-6 and AAV clinical features. Methods: Upon informed consent, clinical data (including disease activity at the time of venepuncture, as estimated by the Bimingham Vasculitis Activity Score, BVAS) and blood samples were collected from 63 consecutive patients with AAV (38 with granulomatosis with polyangiitis, GPA), 15 with eosinophilic granulomatosis with polyangiitis, EGPA, 10 with microscopic polyangiitis, MPA and 57 matched healthy controls (HC). Plasma concentrations of PTX3 and TSG-6 were measured by ELISA and correlated with clinical data. Due to the relatively wide range of TSG-6 levels, logarithmic transformation was applied. Data are expressed as mean ± standard error of mean. Results: PTX3 levels were higher in patients (4.99±1.19) than in HC (1.61±0.15; p=0.008). In patients with AAV PTX3 levels correlated with the BVAS (p=0.026), C-reactive protein levels (p=0.032), white blood cell count (p=0.007) and ANCA titer at the time of blood sample collection (p=0.030). PTX3 levels were higher in patients with pure vasculitic manifestations (9.24±3.91 vs 3.55±0.82 in patients with concomitant granulomatous lesions; p=0.036) and lower in patients with ear-nose-throat (ENT) involvement (p=0.010).TSG-6 levels were lower in AAV patients with ENT involvement (5.77±0.35 vs 4.07±0.76; p=0.021) and correlated with platelet count (p=0.005). PTX3 and TSG-6 leves did not correlate. Conclusions: PTX3 levels reflect disease activity and vasculitic involvement in AAV. TSG-6 could play a role in identifying patients with prominent ENT involvement and defective clearance of platelets during acute inflammation. References: Kallenberg CG. Nat Rev Rheumatol. 2014 Milner C et al. J Cell Sci. 2003 Maugeri N et al. Thromb Res. 2012 Disclosure of Interest: None declared